Challenges, Opportunities, and Management of Entrepreneurship in the COVID-19 Pandemic for the Milenial Generation - Mardetini, Edutivia; Barlian, Ikbal; Fatimah, Siti; Hasmidyani, Dwi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The millennial generation is one of the generations that has entrepreneurial potential and capable using social media, especially in Covid 19 pandemic era. This potential has been utilized by the community but has not been optimal. There are lots of social media, if used maximally, can increase sales turnover. The purpose of this community service is to provide entrepreneurial insight into understanding the challenges, opportunities and business management (especially marketing management) for entrepreneurship through social media. This community service was carried out by means of a webinar with zoom meeting for economic education graduates belonging to the millennial generation with age range of 17-37 years of 15 people. The model used is empowerment with the method of delivering materials. Evaluation is carried out through knowledge tests and questionnaires on the use of social media as a promotional, the difficulties in marketing, capital and entrepreneurial operational costs. The participants’ initial test results averaged 6.00 and the final test average 7.07, an increase of 0.27 with the low category. This increase was accompanied by the use of social media as one of the promotional media, the difficulties in marketing, capital, and entrepreneurial operational costs by 78.56%. In conclusion, this community service activity can provide basic knowledge and stimulate the millennial generation to use social media to be entrepreneurial.